Semantic Analysis of Figurative Language Found in Nikkie Tutorials Product Review - Pegy Eka Pertiwi; Nurma Dhona Handayani (Institut Agama Islam Negeri Palopo, 2023)
This study aims to investigate the figurative language in most popular product review of makeup in Nikki Tutorials in Youtube channel. The data were the existing utterances delivered by the content creator. This research used the theory semantic of figurative language from Perrine (2018) to categorize the utterance that appeared in the data source into the function and reason of figurative language. A qualitative research design was employed in conducting this study followed by document analysis and observation as the instruments. This research used observational method that theorized by Sudaryanto (2015), to collect the data in the product review. The result showed that the kind of figurative language was separated into twelve types there are simile, metaphor, personification, apostrophe, metonymy, symbol, allegory, paradox, overstatement, understatement, synecdoche, and irony and the reason of figurative language specifically imaginative pleasure, bringing additional imagery, additional emotional intensity, and saying in brief compass. Related to the types, the researcher found 42 data that contains the kind of figurative language. There were 21 data of hyperbole, 4 data of simile, 1 data of metaphor, 7 data of personification, 2 data of apostrophe, 1 data of metonymy, 2 data of symbol, 2 data of paradox, 2 data of understatement. Whereas the reason of figurative language, the researchers found 30 data. 25 data increase emotional intensity, 2 data bringing additional imagery, 2 data saying in brief compass, 1 data afford imaginative pleasure. Moreover, the most used in the kind of figurative language is hyperbole whereas the reason of figurative language is increase emotional intensity which always appeared in the data analysis.